Implementasi Kecerdasan Jamak (Multiple Intelegences) pada Model Pembelajaran BCCT atau Sentra pada Pendidikan Anak Usia Dini - Irna Irna (STKIP Muhammadiyah Bogor, 2020)
Multiple intellegences are instructions of Indonesian National Anthem, Indonesia Raya, “.... “Bangunlah Jiwanya, Bangunlah badannya, untuk Indonesia Raya””. To construct multiple intellegences must to be done from childhood, because this is gold periode. The implementation of multiple intellegences in BCCT or Center learning model in childhood education consist of linguistic, logical mathematic, musical, bodily kinesthetic, spatial, interpersonal, intra personal, naturalistic, extensional and spiritual intelligence. These intelligences are implemented in playing activities in centers or BCCT (Beyond Centers and Circle Time) learning model which consist of Block Center, reading and calculating center , creativity center, micro and macro role play center, praying center and natural center.